Induction of Quercus ilex L. haploid and doubled-haploid embryos from anther cultures by temperature-stress (SILVAE GENETICA, 2013)
This paper describes a method to obtain haploid and doubled-haploid (DH) embryos using anther cultures of holm oak (Quercus ilex L.). The production of haploids and DH through gametic embryogenesis provides an attractive biotechnological tool for developing homozygous lines from heterozygous parents, which is important in breeding programs, as well as in genetic studies. As a consequence, protocols to produce homozygous plants have a significant impact on forest tree improvement. Anthers were subjected to different temperature treatments for embryo induction: a cold pre-treatment (4 C) from 3 to 7 days was carried out at the beginning, followed by a heat shock (33 C) from 2 to 5 days. Most anthers responding to these stress treatments contained vacuolated microspores, indicating that this developmental stage is responsive to embryogenesis induction in holm-oak microspores. In all cases, embryos grew from the interior of the anthers, breaking through the degenerating anther walls. Under these conditions, embryo formation occurred in 31 anthers between 46 and 95 days after culture initiation. Embryo analysis performed with flow-cytometry and DNA-microsatellite markers showed haploid profiles and/or spontaneous doubling of the chromosomes during early regeneration stages. This is, to our knowledge, the first published report on gametic embryogenesis in holm oak.